New chitosan derivatives induced resistance to fusarium wilt disease through phytoalexin (Gossypol) production - Omyma A.Awadalla,; Yehia A.-G. Mahmoud, (Universiti Kebangsaan Malaysia, 2005)
The present investigation studied the mechanism of resistance to Fusarium oxysporum f.sp.vasinfectum induced by some chitosan derivatives in susceptible cotton plants. Pretreating cotton seeds with chitosan markedly increased cotton resistance to vascular wilt caused by Fusarium oxysporum f.sp. vasinfectum. The five chitosan derivatives tested repressed the pathogen mycelial growth. Chitosans 3, 4 and 8 had a disease score of 0.5:tO.02, 0.6:tO.5 and 0.0 respectively, indicating that the host plants were free from visual symptoms and that these chitosans were the most effective in controlling Fusarium wilt disease. Phytoalexin (gossypol) production was greatly increased with a maximum of 1.16 mg/5gmfresh root tissue in chitosan-treated plants. The level of gossypol was higher in the roots than in the stems and the maximum production of gossypol was achieved in cotton plants treated with the chitosan 3, 4 and 8 and inoculated with the pathogen spores as compared with uninoculated plants.